Mandatory Mediation of Civil Cases in a Highly Urbanized City - Soriano, Imelda DP; Maniago Jr, Deonido S; A Mendoza, Kristin Joy (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This study assessed the mandatory mediation in civil cases in Olongapo City. It utilized the descriptive-survey research method with the questionnaire as the primary data-gathering tool. Sixty-six (66) respondents participated in the study. The study also used an unstandardized questionnaire validated by a panel of experts. To analyze the data, the researchers utilized the following statistical tools: frequency, percentage, weighted mean, and Pearson Chi-Square test. The study confirms that respondents are highly aware of mediation rules, proceedings, and mediators' code of ethical standards. Results also revealed significant relationships between the level of awareness of the respondents of the mandatory mediation of civil cases and age, the level of awareness of the code of ethical standards with the highest educational attainment, and length of service. In addition, the study also found significant relationships between the profile variables and the extent of implementation. Finally, there was a relationship between the level of awareness and the extent of implementation of the mandatory mediation of civil cases in terms of submitted and disposed cases. The study results served as the basis for developing a Proposed Enhancement Program in implementing Mandatory Mediation of Civil Cases in Olongapo City.